2018
DOI: 10.1155/2018/9040471
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Slurry for Long‐Distance Large‐Diameter Pipe Jacking in Expansive Soil

Abstract: When the pipe jacking technology is applied in expansive formation, the soil around the pipe will easily absorb water from the slurry and expand to wrap up the pipe, producing an excessive pipe jacking force. A water-based slurry formula suitable for pipe jacking in expansive soil layer was proposed in this paper. Firstly, the key design points of pipe jacking slurry in expansive soil were put forward. Secondly, plant glue, potassium humate, Na-CMC, and graphite powder were chosen as treating agents to improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Zhou et al [28] simulated the influence of grouting on jacking force and surface settlement in silt areas and concluded that reasonable control of slurry parameters can effectively reduce friction and control surface settlement. Yang et al [29] also obtained that if the mud performance can be improved, the jacking force in pipe jacking construction can be reduced and the jacking force can be predicted accurately. Sun et al [30] adopted the field monitoring method to analyze the key parameters in the pipe jacking construction of double line underground pedestrian passage and presented geoenvironmental impacts of the rectangular pipe jacking technology.…”
Section: Numerical Simulationmentioning
confidence: 99%
“…Zhou et al [28] simulated the influence of grouting on jacking force and surface settlement in silt areas and concluded that reasonable control of slurry parameters can effectively reduce friction and control surface settlement. Yang et al [29] also obtained that if the mud performance can be improved, the jacking force in pipe jacking construction can be reduced and the jacking force can be predicted accurately. Sun et al [30] adopted the field monitoring method to analyze the key parameters in the pipe jacking construction of double line underground pedestrian passage and presented geoenvironmental impacts of the rectangular pipe jacking technology.…”
Section: Numerical Simulationmentioning
confidence: 99%
“…Friction resistance is the main component of jacking force. Application of lubricant such as bentonite slurry in pipe jacking (that is, the so-called "slurry pipe jacking") is essential to reduce the friction resistance and therefore the jacking force [3,4]. However, it does make it more complex for the calculation or prediction of friction resistance due to the change in contact conditions between the pipe and soil.…”
Section: Introductionmentioning
confidence: 99%
“…The main component of the jacking force is due to frictional resistance. Application of a lubricant such as bentonite slurry in pipe jacking (so-called 'slurry pipe jacking') is essential to reduce the friction resistance and, therefore, the jacking force [3,[10][11][12][13]. However, the use of slurry makes it more complex to calculate or predict the friction resistance because of the change in contact conditions between the pipe and soil and lubricant slurry.…”
Section: Introductionmentioning
confidence: 99%